Transient suppression of transgene expression by means of antisense oligonucleotides: a method for the production of toxin-transducing recombinant viruses - Raykov, Zahari Zahariev; Rommelaere, Jean (Gene therapy, 2002)
Some of the therapeutic genes to be delivered by means of recombinant adenoviruses code for toxic compounds. Expression of these sequences can be deleterious to the complementation cells used for vector production, making it often difficult to generate high-titer stocks of toxin-transducing recombinant adenoviruses. In this work, we present a novel strategy for the transient post-transcriptional down-regulation of toxic transgene expression during the vector production phase, through the administration of phosphorothioate-modified antisense oligodeoxyribonucleotides. This method was successfully applied to the production of hybrid adenoviruses that contain the gene encoding the cytotoxic parvoviral protein NS1. The generation of recombinant adenoviruses in 293T cells was found to be fully suppressed as a result of adding of the NS gene to the vector genome. Yet, the production of NS-harboring hybrid adenoviruses could be rescued by treating the producer cells with antisense oligonucleotides specific for the translation initiation region of the NS transcript. This rescue correlated with a striking reduction of NS RNA and protein levels in the complementation cells. These data provide proof of principle of the suitability of the antisense oligonucleotides strategy for overcoming the interference of harmful transgenes with the production of adenoviral and other vectors.
Gesehen am 16.02.2021